Reducing the burden of Tuberculosis: an emphasis on improving awareness among caregivers - Joshi, Jawahar Lal; Abraham, Jebin; Bhatnager, Arjun; Chungath, Jain Thomas; Girdhar, Nidhi; Bharti, Anu; Kaur, Komaldeep; Sharma, Karan (International Journal of Research in Medical Sciences, 2019)
Background: Tuberculosis (TB) is one of the common communicable disease affecting human beings since ancient times. Though effective chemotherapy emerged during 20th century had raised hope towards eliminating TB burden, it still remains as a distant goal. Awareness about TB among close contacts of active disease is of paramount importance in preventing its spread and promoting early diagnosis and treatment. This study aimed to assess the knowledge about tuberculosis among caregivers of tuberculosis patients. Methods: This was a cross sectional study that enrolled 300 subjects who were then caregivers of tuberculosis patients admitted in the Department of Pulmonary Medicine. Subjects were interviewed according to a predesigned panel of questions meant to assess their basic knowledge and perceptions about tuberculosis symptomatology, diagnostic modalities, treatment and prevention. Results: About 90.3% (n=271) of subjects had heard about TB previously and about 37.7% (n=113) considered themselves to be well aware of it. Most of them believed TB to be communicable (90.3%, n=271). Majority believed that TB affects lungs only (n=206, 68.7%), with most commonly perceived symptom being cough (n=285, 95%). Knowledge regarding disposal of sputum was poor (n=110, 36.7%). About 168 (56%) subjects considered usage of face mask by the patient as an effective tool for TB prevention. Conclusions: Caregivers of tuberculosis patients lack proper knowledge about major aspects of the disease. Public awareness and care giver education programs needs to be implemented along with standard TB care to reduce transmission of TB among close contacts.